Ekologi dan Kelimpahan Ikan Sentani Gudgeon (Oxyeleotris heterodon, Weber 1908) dan Snakehead Gudgeon (Giuris margaritacea, Valenciennes 1837) di Danau Sentani, Papua - Henderite L. Ohee; Gerardinalia Ngamelubun; Joane J. Ansaka; Novela H. Korwa; Puguh Sujarta (Jurusan Biologi FMIPA Universitas Cenderawasih, 2019)
Freshwater community in Lake Sentani comprise of 35 species including three endemic species, seven native species, eight anadromous fish and 17 introduced species. Two native species are Sentani Gudgeon (Oxyeleotris heterodon) and Snakehead Gudgeon (Giuris margaritacea). The survey aims to document the ecology and fish abundance of the gudgeons in Lake Sentani. Fish sampling was done passively by using gill nets with three different mesh sizes in five locations; Puai, Enandowai, Waena, Ayapo and Yahim. Substrate type, water vegetations, habitat depth and fish abundance were recorded each locations. Substrate preferences of the gudgeons are sand, mud and gravel, while O. heterodon was more abundance in sand mud substrate type. Moreover, water vegetation preference was different between O. heterodon and G. margaritacea. Sentani Gudgeon prefer habitat with dense water vegetations, while G. margaritaceus could be found in habitat with or without water vegetation. Theses two gudgeons were found in relatively the same habitat depth, up to 7 meters depth. O. heterodon and G. margaritacea had a very low abundance in the lake. It is important to conserve lake area from the edge up to 7 meter depth that consist of sand, mud and gravel substrate types and dense water vegetation to ensure the population of these two gudgeons are abundance in Lake Sentani. Key words: Ecology, Lake Sentani, relative abundance, O. heterodon, G. margaritacea.